The use of dissociated crinoid ossicles as biostratigraphical and palaeoecological tools in the Carboniferous of northwest Ireland - Mannifield, Kay (Trinity College (Dublin, Ireland). Department of Geology, 2001)
Fossil crinoids were investigated from the Lower Carboniferous (Visean) rocks of northwest Ireland. In this area the deltaic Mullaghmore Sandstone Formation stratigraphically separates the Bundoran Shale Formation (Arundian) and the Benbulben Shale Formation (Holkerian-Asbian). These two formations are similar lithologically consisting of clay-rich, calcareous shale interbedded with discontinuous beds, and lenses of bioclastic, often argillaceous limestone. The sedimentary sequence represents the incursion of a fluviodeltaic complex into the Carboniferous sea of northwest Ireland and its subsequent retreat. The Bundoran Shale Formation records the progradation of the delta over prodelta muds, and the Benbulben Shale Formation represents a major flooding surface on the subsequent receding delta. Although several horizons throughout the succession have been sampled, the study concentrated particularly on these two formations since they yielded countless fossil crinoid specimens.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin